2021
DOI: 10.3390/jcm10071518
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Robotics in Pelvic Exenteration Surgery for Locally Advanced Rectal Cancer: A Narrative Review

Abstract: Pelvic exenteration surgery for locally advanced rectal cancers is a complex and extensive multivisceral operation, which is associated with high perioperative morbidity and mortality rates. Significant technical challenges may arise due to inadequate access, visualisation, and characterisation of tissue planes and critical structures in the spatially constrained pelvis. Over the last two decades, robotic-assisted technologies have facilitated substantial advancements in the minimally invasive approach to tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Furthermore, the rectum and colon have different anatomical locations, with the pelvis being an especially difficult area to work in laparoscopically owing to its narrow cavity and depth. For rectal pathologies, robotic surgery offers greater depth perception, 30 superior rotation, and acute angulation, creating a bigger work space compared to laparoscopic surgery 31 . These benefits are not as well defined in robotic colon surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the rectum and colon have different anatomical locations, with the pelvis being an especially difficult area to work in laparoscopically owing to its narrow cavity and depth. For rectal pathologies, robotic surgery offers greater depth perception, 30 superior rotation, and acute angulation, creating a bigger work space compared to laparoscopic surgery 31 . These benefits are not as well defined in robotic colon surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic pelvic exenteration has been associated with reduced blood loss, faster recovery and an acceptable length of stay; on the contrary, in well-selected patients, the learning curve is steep [ 92 ]. Robotic-assisted surgery facilitates a more ergonomic and visually enhanced platform [ 93 ].…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%
“…This study demonstrated the safety and feasibility of MIS exenteration in patients with favourable anatomy and tumour characteristics [ 1 ]. Moving forward, novel robotic technology such as fluorescence-guided surgery, 3-dimensional modelling and stereotactic navigation will significantly improve surgical dissection and resection margins [ 93 ]. Fluorescence-guided surgery was established in several different specialities.…”
Section: Contemporary Management Strategiesmentioning
confidence: 99%
“…Patients who underwent pelvic exenteration have a low 5-year survival rate according to early literature. Along with the confirmation of surgical indications, mastery of surgical techniques, and improved diagnosis and treatment for perioperative complications, the postoperative 5-year survival rate has increased from 20% in an earlier period to 64% [ 5 ]. A systematic review indicated that a positive surgical margin is an important prognostic indicator in pelvic exenteration.…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic exenteration is a complicated procedure with intraoperative and postoperative comorbidity-related mortality rate of 0–12%. Previous studies have shown that the survival rates of patients with postoperative complications is significantly reduced [ 5 ]. Resection of pelvic tissues that receive radiotherapy may lead to various fistulas, poor wound prognosis, and secondary problems caused by ureteral or intestinal obstruction.…”
Section: Introductionmentioning
confidence: 99%